2006
DOI: 10.1063/1.2349603
|View full text |Cite
|
Sign up to set email alerts
|

In situ deformation apparatus for time-of-flight neutron diffraction:Texture development of polycrystalline ice Ih

Abstract: This article documents a new in situ deformation apparatus built for neutron diffraction investigations of polycrystalline materials in low-temperature environments and the first experiment in which it was used. We performed texture analysis of fine-grained polycrystalline D2O ice Ih deformed uniaxially between 230 and 240K using time-of-flight neutron diffraction on the high-pressure preferred orientation diffractometer at the Manuel Lujan, Jr. Neutron Scattering Center at Los Alamos National Laboratory. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…All experiments (Table 2) have used a matrix of deuterated ice (D 2 O), as this allows quantitative in situ neutron diffraction and grain size analysis during deformation. D 2 O has the same crystal structure, similar mechanical properties, and deformation behaviour as H 2 O ice (Petrenko and Whitworth, 1999; McDaniel and others, 2006; Wilson and others, 2014; Middleton and others, 2017). Undeformed samples of deuterated ice were prepared by crushing and mixing 180–250 µm sieved ice particles with liquid D 2 O at −10 to −5°C within moulds.…”
Section: Methodsmentioning
confidence: 99%
“…All experiments (Table 2) have used a matrix of deuterated ice (D 2 O), as this allows quantitative in situ neutron diffraction and grain size analysis during deformation. D 2 O has the same crystal structure, similar mechanical properties, and deformation behaviour as H 2 O ice (Petrenko and Whitworth, 1999; McDaniel and others, 2006; Wilson and others, 2014; Middleton and others, 2017). Undeformed samples of deuterated ice were prepared by crushing and mixing 180–250 µm sieved ice particles with liquid D 2 O at −10 to −5°C within moulds.…”
Section: Methodsmentioning
confidence: 99%
“…D 2 O ice is used as a replacement for H 2 O in experiments carried out in neutron beamlines (e.g. [23][24][25][26][27]), where replacement of H 2 O by D 2 O is necessary to avoid incoherent scattering of the diffracted beam [28,29]. These in situ studies have allowed the evolution of texture during deformation to be observed, and grain-scale changes linked to the dominant deformation mechanism to be identified [26].…”
Section: Introductionmentioning
confidence: 99%
“…The information derived from the diffraction data is averaged over a large volume ͑typically in the order of a cubic centi-meter͒; therefore, sampling statistically significant numbers of grains even in coarse-grained aggregates and special sample environments are possible. Time-of-flight ͑TOF͒ neutron diffraction is increasingly used to record textures of bulk materials, providing the additional advantage of determining textures of low symmetry phases ͑e.g., Brown et al, 2006;Xie et al, 2003͒, of composites with complex diffraction patterns ͑e.g., Ivankina et al, 2005;Wenk et al, 2001͒, or in situ experiments at high/low temperature ͑e.g., Bhattacharyya et al, 2006;Lonardelli et al, 2007;McDaniel et al, 2006;Wenk et al, 2007͒ andstress ͑Hartig et al, 2006͒. Since the Rietveld approach ͑Rietveld, 1969͒ is used to extract the texture information, it does not rely on single wellresolved diffraction peaks, as pole figure gonio metersdo, which are used for constant wavelength neutrons or X-rays. Neutron diffraction is most efficient with multidetector spectrometers such as high pressure preferred orientation ͑HIPPO͒ ͑at LANSCE, Los Alamos; Vogel et al, 2004;Wenk et al, 2003͒, GEM ͑at ISIS, U.K.;Day et al, 2004͒, or SKAT ͑at the Joint Institute for Nuclear Research, Russia; Ullemeyer et al, 1998͒, where each detector records a spectrum of crystals with lattice planes in reflection orientation.…”
Section: Introductionmentioning
confidence: 99%